1978
DOI: 10.1007/bf01921925
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of viable endothelial cells in cultures derived from dissociated rat brain

Abstract: The morphology and histochemistry of dissociated newborn rat brain was studied in tissue culture. Direct microscopy of developing cells, electron microscopy and the alkaline phosphatase activity were used to identify the capillary endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(29 citation statements)
references
References 4 publications
1
27
0
1
Order By: Relevance
“…The most widely used methods of determining the identity of these cells have been histochemi cal detection of alkaline phosphatase and yglutamyl transpeptidase activities [10,15,22,28]. We have confirmed that endothelial cells in cryostat sections do indeed appear to con tain much higher levels of alkaline phospha tase activity than the neural cell types, al though electron microscopic studies have shown that the enzyme is not found solely in endothelial cells [29].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The most widely used methods of determining the identity of these cells have been histochemi cal detection of alkaline phosphatase and yglutamyl transpeptidase activities [10,15,22,28]. We have confirmed that endothelial cells in cryostat sections do indeed appear to con tain much higher levels of alkaline phospha tase activity than the neural cell types, al though electron microscopic studies have shown that the enzyme is not found solely in endothelial cells [29].…”
Section: Discussionsupporting
confidence: 61%
“…Several authors have recently reported the growth of brain endothelial cells in dis persed cell culture [9,10,15,22,28]. The most widely used methods of determining the identity of these cells have been histochemi cal detection of alkaline phosphatase and yglutamyl transpeptidase activities [10,15,22,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past few years, several laboratories have developed methods for culturing endothelial cells from brain microvessels 11 1, 24, 63,68,76). In this issue of the Annals, Bowman and colleagues 112) describe some of the features of cultured endothelial cells prepared from bovine brain.…”
Section: Cultured Brain Capillary Endothelial Cellsmentioning
confidence: 95%